Analisis rancang bangun PLTS ON-Grid hibrid baterai dengan PVSYST pada kantin teknik FTUI - Faiz Husnayain (Electrices, 2020)
This paper aims to investigate the feasibility and viability of the on-grid solar power generation at the university canteen by using two alternative methods. The first method uses the actual daily load as the basis of the calculation for the reliability of the system, whilst, the second method uses the available area as the basis of the calculation of the power generation. This research analyses the technical feasibility and the economic viability of each possible configuration involved in the comparison process. The analysis shows that the on-grid configuration set by using the maximum available area for power generation provides the highest economic viability. The system may contribute to nearly 68.98% of the working day energy consumption and nearly 182.18% of the consumption during the weekend. The total energy generation is expected to reach the potential of 16.063kWh annually.